Maternal and foetal adverse events with tumour necrosis factor‐alpha inhibitors in inflammatory bowel disease. Issue 9 (28th August 2014) - Deepak, P.; Stobaugh, D. J.
Summary Background Transplacental transfer of tumour necrosis factor‐alpha (TNF‐α) inhibitors has been shown in mothers receiving therapy for inflammatory bowel disease (IBD). Aim To examine reports of adverse events of these medications in pregnancy. Methods Individual Safety Reports of adverse events (Jan 2003–June 2012) were accessed from the Food and Drug Administration Adverse Event Reporting System. The study data set was constructed by searching for cases with an indication for medication usage of IBD. The data set was then queried for key terms indicating pregnancy, followed by elimination of cases with potentially teratogenic exposures (FDA category X concomitant medications) as well exposures to study medications through partner or if the medications were discontinued prior to pregnancy. Logistic regression analysis was performed to detect signals for maternal/foetal adverse events with TNF‐α inhibitors and/or thiopurines (compared to aminosalicylates). Results A total of 1097 individual Safety Reports in pregnant IBD patients were identified with the majority reported among patients receiving TNF‐α inhibitor monotherapy (783 cases, 71.4%). Thiopurine monotherapy (OR 2.55, CI 0.95–6.88) and in combination with TNF‐α inhibitors (OR 0.97, CI 0.49–1.93) were not associated with increased odds of maternal/foetal adverse events. Decreased odds for maternal/foetal adverse events were seen with TNF‐α inhibitor monotherapy (overall) and specifically with certolizumab monotherapy (OR 0.11, CI 0.05–0.23). Conclusions In this analysis of adverse events from the Food and Drug Administration Adverse Event Reporting System, use of thiopurine monotherapy or in combination with TNF‐α inhibitors was not associated with an increase in maternal/foetal adverse events. Certolizumab monotherapy was associated with a decrease in maternal/foetal adverse events.